“All things equal”: ethical principles governing why autonomous vehicle experts change or retain their opinions in trolley problems—a qualitative study - Milford, Stephen R.; Malgir, B. Zara; Elger, Bernice S.; Shaw, David M. (Frontiers in Robotics and AI, 2025)
IntroductionAutonomous vehicles (AVs) are already being featured on some public roads. However, there is evidence suggesting that the general public remains particularly concerned and skeptical regarding the ethics of collision scenarios.MethodsThis study presents the findings of the first qualitative research into the ethical opinions of experts responsible for the design, deployment, and regulation of AVs. A total of 46 experts were interviewed in this study and presented with two trolley-problem-like vignettes. The experts were asked for an initial opinion on the basis of which the parameters of the vignettes were changed to gauge the principles that would result in either changing or retaining an ethical opinion. Much research has been conducted on public opinion, but there are no available research findings on the ethical opinions of AV experts.ResultsFollowing reflective thematic analysis, four important findings were deduced: 1) although the expert opinions are broadly utilitarian, they are nuanced in significant ways to focus on the impacts of collision scenarios on the community as a whole. 2) Obeying the rules of the road remains a significantly strong ethical opinion. 3) Responsibility and risk play important roles in how AVs should handle collision situations. 4) Egoistic opinions were present to a limited extent.DiscussionThe findings show that the ethics of AVs still pose a serious challenge; furthermore, while utilitarianism appears to be a driving ethical principle on the surface, along with the need for both AVs and vulnerable road users to obey the rules, questions concerning community impacts and risk vs. responsibility remain strong influences among AV experts.